The role of teachers in instilling religious character in children aged 5-6 years in kindergarten - Hidayatun, Linda; Sumiadi, Raden; Marzoan, Lalu (Nashir Al-Kutub Indonesia, 2025)
The research aimed to explore how the use of ice-breaking activities affected student engagement and participation in the learning process. Specifically, it focused on how ice breaking was implemented at the beginning, middle, and end of lessons and the impact it had on creating a more enthusiastic and enjoyable learning atmosphere. This qualitative, phenomenological research aimed to provide insights into the effectiveness of ice-breaking games in fostering a more interactive and motivating classroom environment. The research was conducted in class 4 of elementary school during the second semester of the 2023/2024 academic year with a total of 35 students. This was qualitative research using phenomenological methods. Data collection techniques included observation, interviews, and documentation. The data collected were tested for credibility through extended observations during the research, increasing persistence and accuracy, carrying out triangulation, conducting negative case analysis, referencing materials related to the research, and conducting member checks. The results of this research showed that there was an increase in interest in learning for grade 4 students at elementary school through the use of ice-breaking games. The focus of the grade 4 teacher was to implement ice breaking at the beginning, middle, and end of lessons in a planned manner. As a result, by using the ice-breaking game, students became more enthusiastic in participating in the learning process, and the learning atmosphere became more enjoyable.